PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN KINEMASTER APPLICATION MATERI BAGIAN TUBUH TUMBUHAN UNTUK SISWA KELAS IV SD - Estuhono Estuhono; Muhammad Subhan; Ria Hopipah (Jurnal Muara Pendidikan, 2023)
This writing is motivated by the inaccuracy of tha selection of instructional video media on the material of plant body parts in class IV SD Negeri 82 Rantau Limau Kapas, Merangin Regency. Inappropriate learning videos are not able to fully accommodate student’s learning styles. This writing aims to produce a product in the form of a valid, practical, and effective learning videos for material on plant body parts in class IV. The type of research conducted is development research. This research uses the ADDIE development model. The test subjects in this study fourth grade students at SD Negeri 82 Rantau Limau Kapas and fourth grade science teachers. The research conducted shows that the instructional video media using the kinemaster application that was developed is valid, practical, and effective. So it can be concluded that from the process of developing learning videos using the kinemaster application, material on plant body parts to support independent learning for fourth grade students has produced media that (1) valid, both in terms of aspects as media, language aspects, and material aspects, (2) media that is practically used both from the aspects of students and educators, and (3) has produced effective media to achieve learning objectives according to the curriculum.